Dynamic simulation of 3D weaving process - Yang, Xiaoyan (Kansas State University, 2015)
Textile fabrics and textile composite materials demonstrate exceptional mechanical properties, including high stiffness, high strength to weight ratio, damage tolerance, chemical resistance, high temperature tolerance and low thermal expansion. Recent advances in weaving techniques have caused various textile fabrics to gain applications in high performance products, such as aircrafts frames, aircrafts engine blades, ballistic panels, helmets, aerospace components, racing car bodies, net-shape joints and blood vessels. Fabric mechanical properties are determined by fabric internal architectures and fabric micro-geometries are determined by the textile manufacturing process. As the need for high performance textile materials increases, textile preforms with improved thickness and more complex structures are designed and manufactured. Therefore, the study of textile fabrics requires a reliable and efficient CAD/CAM tool that models fabric micro-geometry through computer simulation and links the manufacturing process with fabric micro-geometry, mechanical properties and weavability. Dynamic Weaving Process Simulation is developed to simulate the entire textile process. It employs the digital element approach to simulate weaving actions, reed motion, boundary tension and fiber-to-fiber contact and friction. Dynamic Weaving Process Simulation models a Jacquard loom machine, in which the weaving process primarily consists of four steps: weft insertion, beating up, weaving and taking up. Dynamic Weaving Process Simulation simulates these steps according to the underlying loom kinematics and kinetics. First, a weft yarn moves to the fell position under displacement constraints, followed by a beating-up action performed by reed elements. Warp yarns then change positions according to the yarn interlacing pattern defined by a weaving matrix, and taking-up action is simulated to collect woven fabric for continuous weaving process simulation. A Jacquard loom machine individually controls each warp yarn for maximum flexibility of warp motion, managed by the weaving matrix in simulation. Constant boundary tension is implemented to simulate the spring at each warp end. In addition, process simulation adopts re-mesh function to store woven fabric and add new weft yarns for continuous weaving simulation. Dynamic Weaving Process Simulation fully models loom kinetics and kinematics involved in the weaving process. However, the step-by-step simulation of the 3D weaving process requires additional calculation time and computer resource. In order to promote simulation efficiency, enable finer yarn discretization and improve accuracy of fabric micro geometry, parallel computing is implemented in this research and efficiency promotion is presented in this dissertation. The Dynamic Weaving Process Simulation model links fabric micro-geometry with the manufacturing process, allowing determination of weavability of specific weaving pattern and process design. Effects of various weaving process parameters on fabric micro-geometry, fabric mechanical properties and weavability can be investigated with the simulation method.
Keywords: Textile/Fabric; Finite element analysis; Digital element approach; Weaving process simulation; Mechanical Engineering (0548)